Dampak Aktivitas Wisata Bahari Terhadap Kondisi Ekosistem Terumbu Karang Di Gili Labak, Madura - Nirmalasari Idha Wijaya; Viv Djanat Prasita (Faculty of Science and Technology University Ibrahimy, 2024)
Gili Labak is a small island in Sumenep Regency. The area of ​​the island is only ± 5 ha, of which 2.1 ha is a stretch of white sand. The width of the white sand beaches surrounding Gili Labak Island is an average of 20 meters wide, with a coastline of 1,200 meters, providing a wide and comfortable beach tourism area for visitors. The coral reef ecosystem on Gili Labak Island, which is in good condition, covers an area of ​​80.99 ha. This research aims to evaluate the impact of marine tourism activities on coral reef ecosystems. Research was conducted using qualitative and quantitative methods. In this research qualitative methods were used related to tourism activities. The quantitative research method used is a survey method to observe the condition of the coral reef ecosystem on Gili Labak Island, and collect spatial data and attribute data. To determine the impact of tourism on the island of Gili Labak, a questionnaire survey was used to determine the demographics of visitors, their activities on the island. The results of observations of oceanographic conditions obtained in 2019 versus 2023 oceanographic data are not too different. The condition that is very different is the coral cover which tends to decrease. Coral life forms tend to be stable, but there is a decrease in the number of life forms at station 2 which is located on the west side of the island. The results of observations on habitat resilience show that all habitats have high resistance to natural disturbances, but changes in land area and habitat structure easily occur due to human activities, such as marine tourism and fishing boats. Marine tourism activities contribute greater pressure to coral reefs than fishing activities.